(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2013)
Objective: The study was intended to determine the angiographic profile (severity, site, and type of lesion) based on the level of cardiac troponin-I (cTn-I) in patients of unstable angina. Methods: The present cross-sectional study was conducted in the Department of Cardiology, Sir Salimullah Medical College & Mitford Hospital (SSMCH). Data were collected at Ibrahim Cardiac Hospital & Research Institute and SSMCH. A total of 81 patients with unstable angina were selected over a period of 1 year. Based on the level of cTn I at admission, the patients were divided into high risk (troponin-I level 0.060.6) and low-risk (0<0.06) groups. Thus 47patients fell into high risk group (Group-I) and 34 patients into low-risk group (Group-II). The angiographic characteristics of the two groups of patients were then compared. Results: Over three-quarter (77%) of the patients in Group-I had significant coronary lesions compared to 26% in Group-II. Significant stenosis was commonly observed in Group-I than that in Group-II (p < 0.001). Number of vessels involved like single vessel (SVD), double vessel (DVD), and triple vessel diseases (TVD) were higher in Group-I compared to Group-II (30% vs. 20%; 34% vs. 3% and 12% vs. 3%). Site of lesions in LAD (left anterior descending) were compared between the study groups, proximal and mid lesions were found significantly higher in Group-I (45% vs. 9% and 49% vs. 18%, respectively), while distal lesion was almost identically distributed (5% vs. 6%). Type-B land type C lesions were higher in Group-I (30% vs. 3.0%) and (47% vs. 14%) while type-A lesion was higher in the Group-II (20% vs.8%). Majority (77%) of the patients who developed significant coronary artery lesion had raised cTnI. Conclusions: Patients of unstable angina with raised serum troponin-I had more severe coronary lesions (in terms of number of vessels significantly affected and site and type of lesions) than those with low serum troponin-I. DOI: http://dx.doi.org/10.11566/cmoshmcj.v12i2.33 Chatt Maa Shi Hosp Med Coll J 2013; 12(2): 13-18